Occurrence of multidrug-resistant Acinetobacter baumannii and Escherichia coli in veterinary health care facilities - Ng, Joanna Sze Yi (2015)
Multidrug-resistant organisms (MDROs) such as multidrug-resistant (MDR) Acinetobacter baumannii and Escherichia coli are important pathogens associated with nosocomial infections in both human and animal health care settings. Surfaces of inanimate objects in health care facilities can serve as important sources of infection. However, studies on prevalence of these pathogens in veterinary settings are lacking in the country. Therefore, the objectives of this study were to determine the occurrence of A. baumannii and E. coli and the occurrence of MDR isolates on surfaces of inanimate objects from veterinary health care facilities in Klang Valley, Malaysia. In this study, swab samples were taken from 65 surfaces of inanimate objects which included door knobs, examination tables, labcoats, stethoscopes and weighing scales in veterinary health care facilities. The swab samples were cultured and all isolates were subjected to antibiotic susceptibility testing. Results of this study revealed the occurrence of A. baumannii was 9.23% and five out of six A. baumannii isolates (83.33%) were classified as MDR. However, no E. coli was isolated. In conclusion, surfaces of inanimate objects can be a source of MDR A. baumannii in veterinary health care facilities.